PENERAPAN MODEL PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Hikma Wardani; Mahluddin; Fitri Nauli Siagian (STKIP Subang, 2024)
This research aims to evaluate the improvement of mathematics learning outcomes among fourth-grade students at SD Negeri 52/X Rano by implementing the Problem solving teaching model. The method used is Classroom Action Research (CAR), with data collection through observation, tests, and documentation. The study consists of two cycles, each comprising four stages: planning, action implementation using the Problem solving model, observation of teacher and student activities, and reflection on student learning outcomes. The research findings indicate several key points: (1) Teacher activities in managing learning with the Problem solving model significantly improved from 72.5% in the first cycle to 87.5% in the second cycle, (2) Student engagement also increased from 58.3% in the first cycle to 85.4% in the second cycle, and (3) Student learning achievement improved from an average of 68.5 in the first cycle to 85 in the second cycle. Thus, the implementation of the Problem solving model has proven effective in enhancing mathematics learning outcomes for fourth-grade students at SD Negeri 52/X Rano.